The implementation of “The St. Gallen Model for Destination Management (SGDM)” in the Polish Carpathians: A case study of six Bieszczady communes - Klimek, Katarzyna (Turyzm/Tourism, 2019)
The Bieszczady mountains are one of the ranges of the Polish Carpathians. Their natural and cultural amenities attract thousands of Polish and international tourists each year. Despite many protected zones existing in this area (e.g. Bieszczadzki National Park, UNESCO Biosphere Reserve and Nature 2000 areas), the Bieszczady mountains face various environmental and social problems which have arisen from their dynamic but often chaotic tourism development. The lack of a common vision of long-term tourism development (on communal and regional levels) is one of the main challenging issues which public and private bodies are confronted with. The paper presents the results of the implementation of an innovative approach, i.e. the St. Gallen Model for Destination Management (SGDM), in selected Bieszczady communes. This method offers a clear advantage for key destination actors by allowing them to enter a process of holistic destination management. The article is the first attempt at SGDM application in Poland.